Imprints of the Einasto density profile and complexity factor on traversable wormholes in f(R, T) theory - Tayyab Naseer; M. Sharif; Mona Faiza; Baiju Dayanandan (European Physical Journal C: Particles and Fields)
Abstract The focus of this work is centered on determining whether traversable wormholes admitting Einasto density profile exist within the framework of f(R, T) gravity. Using the Morris–Thorne spacetime, we express the wormhole configuration and formulate the anisotropic gravitational equations for a particular linear modified model. Afterwards, by considering two different (constant and variable) redshift functions, we derive the shape function for wormholes and examine its potential stability. The developed functions conform to the necessary conditions and form a connection between two spacetime regions that are asymptotically flat. We also examine the viability of resulting wormhole solutions by verifying their violation with the null energy conditions. We also investigate the active gravitational mass and the complexity factor for our solutions. The later quantity is found to be negative near the wormhole throat and becomes zero when moving away from this point. Further, various methods of stability analysis are utilized to assess the developed models. Our results suggest that the constructed wormhole geometries meet the necessary conditions, thereby existing within the considered modified gravity.